Cross-sensory correspondences and symbolism in spoken and written language - Walker, Peter * (American Psychological Association, 2016)
Lexical sound symbolism in language appears to exploit the feature associations embedded in cross-sensory rrespondences. For example, words incorporating relatively high acoustic frequencies (i.e., front/close rather than back/open vowels) are deemed more appropriate as names for concepts associated with brightness, lightness in weight, sharpness, smallness, speed and thinness, because higher pitched sounds appear to have these cross-sensory features. Correspondences also support prosodic sound symbolism. For example, speakers might raise the fundamental frequency of their voice to emphasise the smallness of the concept they are naming. The conceptual nature of correspondences and their functional bi-directionality indicate they should also support other types of symbolism, including a visual equivalent of prosodic sound symbolism. For example, the correspondence between auditory pitch and visual thinness predicts that a typeface with relatively thin letter strokes will reinforce a word's reference to a relatively high pitch sound (e.g., squeal). An initial rating study confirms that the thinness-thickness of a typeface's letter strokes accesses the same cross-sensory correspondences observed elsewhere. A series of speeded word classification experiments then confirms that the thinness-thickness of letter strokes can facilitate a reader's comprehension of the pitch of a sound named by a word (thinner letter strokes being appropriate for higher pitch sounds), as can the brightness of the text (e.g., white-on-grey text being appropriate for the names of higher pitch sounds). It is proposed that the elementary visual features of text are represented in the same conceptual system as word meaning, allowing cross-sensory correspondences to support visual symbolism in language.